Test-retest reliability of physical fitness tests among young athletes: The FITescola® battery - Henriques-Neto, D.; Minderico, C.; Peralta, M.; Marques, A.; Sardinha, L. B. (Clinical Physiology and Functional Imaging, 2020)
Monitoring physical fitness in young athletes is essential to improve physical performance, identify talents, and develop injury prevention programs. The aim of this investigation was to analyze the reliability of the physical fitness tests from the FITescola® battery in young athletes with different sports backgrounds and competition levels. Participants comprised of 138 young athletes (boys n=92) aged 9 and 18 years old. Eight physical fitness tests assessing six components of physical fitness were performed: cardiorespiratory fitness (PACER); upper body muscular fitness (push-up); flexibility (sit-and-reach); lower body muscular fitness (horizontal and vertical jump); agility (4x10 shuttle run); and speed ( sprint at 20m and 40m). Each test was performed twice, with a one-week interval (7 days) between duplicate tests. No differences between duplicate tests were found (p>0.05), except for the speed at 20m in boys (p<0.001) and speed at 40m in girls (p=0.006). The battery of tests had good or excellent reliability and concordance of the ICC between the two trials (ICC=0.75) with exception for the 20m speed run in girls that presented moderate reliability (ICC = 0.57). The Bland-Altman plots showed high reliability for all the fitness tests for both sexes. Hence, The FITescola® battery may be a novel tool to assess the physical fitness of large groups of young athletes from different sports backgrounds.